The protective effects of erythropoietin on photoreceptor damage by formaldehyde - Khoshnood, Mehdi Mard; Zareie, Mohammad; Amiri, Ali; Zarenezhad, Ali; Zarenezhad, Elham; Esfandiari, Arash (Nepalese Journal of Ophthalmology, 2016)
Introduction: The photoreceptor layer of retina has important role for sight. The previous study showed that accidental formaldehyde injection caused ischemia and damage in the retina. On the other hand the erythropoietin prevents neuronal injury of ischemic damage. Objectives: The aim of this study was to survey the effect of erythropoietin on retro bulbar formaldehyde injected photoreceptor layer of rat retina. Materials and methods: 30 adult rats were used and divided into three groups: 1- control group, 2- formaldehyde group (1 ml retro bulbar injected by 10% formaldehyde solution), 3- erythropoietin group (5000 units/kg immediately intraperitoneally injected by erythropoietin after formaldehyde injection for 7 days). The photoreceptor layer of retina studied using a transmission electron microscope. Results: Our observation showed that disorganization and vacuolization in outer segment and inner segment, pyknotic and karyolysis in outer nuclear layer were seen in formaldehyde group. But the minor sign of pathology such as lightly vacuolization in inner segment were obvious in erythropoietin group. Conclusion: We concluded that formaldehyde caused damage in photoreceptor layer and erythropoietin was improvement this injury. Nepal J Ophthalmol 2016; 8(15): 10-17